EVALUATION OF PHYSICOCHEMICAL CHARACTERISTICS AND DETECTION OF MOST TYPE ADULTERANT OF UHT MILK SOLDS IN THE MARKETS OF ERBIL CITY - HAMEED, ASHTI NAJMADEEN; NANAKALI, NARIN MOHEMMEDAMIN; MUHAMMED, DERIN OMER (Journal of Duhok University, 2023)
Developing countries are considered to be more susceptible to food adulteration, including milk to a large extent, as this is a global concern of the risks associated with it. Due to the lack of monitoring, adulterous milk can pose serious health risks leading to fatal diseases. In this study, the samples were collected from several supermarkets and minimarkets in Erbil city, the capital of the Kurdistan region of Iraq. 100 cans of UHT whole cow milk from four available market brands, for each brand 25 samples, this research reviews some of the common physicochemical properties and adulterous substances in milk and different methods for detecting these adulterous substances in terms of quality and quantity. The results of the research showed that there were highly significant differences for most of the studied physiochemical characteristics except for the percentage of fat and protein. The results showed high contrast for most of the studied characteristics, whether the contrast was negative or positive. As for the results of adulteration, all studied samples were completely free of detergents. While the results of the research showed that all samples were adulterated by adding glucose and skim milk. The COB and alcohol test results (0%,0%,0%, and 4%) were positive for the four brands (1,2,3,4), respectively. As for the percentage of adulterate for the four brands (1,2,3,4) the Formalin was (16%,16%,12%, and 12%), respectively, while the percentage of peroxide was (12%,36%,32%, and 28%), respectively, and all brand samples are completely free of sodium carbonate, except for brand 2, as the rates of this type of adulteration amounted to 16%